2020
DOI: 10.3390/nu12030811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Luteolin and Apigenin on the Production of Il-31 and Il-33 in Lipopolysaccharides-Activated Microglia Cells and Their Mechanism of Action

Abstract: Microglia cells are resident cells of the central nervous system (CNS) charged with modulating inflammation in the CNS. Overstimulation of microglia cells continuously releases inflammatory mediators that contribute to neurodegenerative diseases. Apigenin and Luteolin are flavonoids with reported anti-inflammatory activities. However, their effects on IL-31 and IL-33 production in microglial cells are unknown. Here, we investigated the effects of apigenin and luteolin on the production of IL-31 and IL-33 by mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Their effect on cytokines/chemokines release, such as TNF-α, IL-1β, IL-6, IL-8, IL-10, MCP-1, also reactive oxygen species (ROS) and nitric oxide (NO) production by peripheral blood mononuclear cells and macrophages was demonstrated [3,7,8]. Flavonoids such as apigenin and luteolin were described as able to inhibit inflammation in central nervous system via suppression the activity/release of inducible nitric oxide synthase (iNOS), cyclooxygenase 2 (COX-2), TNF-α IL-1β, IL-6, IL-31, and IL-33 produced by microglia cells [9]. However, since oral (e.g., as infusions, solutions, pellets) or topical (e.g., as creams, ointments, backfills) administration is usually recommended for most of plant extracts containing preparations, intestinal mucous and skin are the first surfaces exposed to such products.…”
Section: Introductionmentioning
confidence: 99%
“…Their effect on cytokines/chemokines release, such as TNF-α, IL-1β, IL-6, IL-8, IL-10, MCP-1, also reactive oxygen species (ROS) and nitric oxide (NO) production by peripheral blood mononuclear cells and macrophages was demonstrated [3,7,8]. Flavonoids such as apigenin and luteolin were described as able to inhibit inflammation in central nervous system via suppression the activity/release of inducible nitric oxide synthase (iNOS), cyclooxygenase 2 (COX-2), TNF-α IL-1β, IL-6, IL-31, and IL-33 produced by microglia cells [9]. However, since oral (e.g., as infusions, solutions, pellets) or topical (e.g., as creams, ointments, backfills) administration is usually recommended for most of plant extracts containing preparations, intestinal mucous and skin are the first surfaces exposed to such products.…”
Section: Introductionmentioning
confidence: 99%
“…Apigenin (4′,5,7-trihydroxyflavone) and galangin (3,5,7-trihydroxy flavones) are the two main flavonoids of yellow chaste weed [ 39 , 40 ]. They have been reported to possess anti-cancer, antioxidant, and anti-inflammatory properties [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]. Although the biological properties of apigenin and galangin have already been extensively studied, it remains unclear how they affect blue light-irradiated HaCaT cells.…”
Section: Introductionmentioning
confidence: 99%
“…Apigenin and luteolin were able to suppress the production of IL-33 by inhibiting its gene and protein expression in the microglia cells. They acted mainly on MAPKs, NF-κB, and STAT3 signalling pathways in LPS-activated microglial cells [ 16 ]. Also, the chromatin remodeling protein, BRG1, possesses the ability to regulate the transcription of IL-33 in endothelial cells.…”
mentioning
confidence: 99%
“…Fundamental for immune-related diseases, IL33 has a key role in controlling inflammation. On one side, Apigenin, Luteolin and immunotherapies demonstrated they efficacy in reducing the interleukin expression by acting on MAPKs, NF-κB, and STAT3 [ 16 , 25 ]. On the other side, most of the authors reported that several genes (BRG1, HDAC3, DND1, PET100, GPR160, LPAR6, SERTAD3, Rip2, NLRP3) are linked to IL-33 levels, although the exact correlation have to be clarified [ 17 19 , 22 , 23 ].…”
mentioning
confidence: 99%